Pengaruh penambahan SBR bervariasi pada perapat pintu air - Pramono, Pramono; Musthofa, Hadi (Majalah Kulit, Karet, dan Plastik, 1994)
The aim of research is to find out the effect of styrene butadiene rubber used to the tensile strength, compression set, and the Hardness of the seal. The variation of styrene butadiene rubber are 20, 30 and 40 phr; Statistical analysis Paint out that there is signify difference often tensile strength but unsignify difference at the compression set and hardness.